Ageing, sex differences, and REDs risk in endurance runners: an integrated cross-sectional study protocol - Oreská, L.; Kundeková, B.; Varga, L.; Stebelová, K.; Okuliarová, M.; Payer, J.; Sedliak, M. (Sports, 2026)
Endurance performance is influenced by age- and sex-specific physiological determinants, while emerging evidence indicates an increasing prevalence of Relative Energy Deficiency in Sport (REDs) among both young and master endurance runners. Despite its clinical relevance, limited data exist on how long-term endurance training modulates REDs risk, skeletal muscle characteristics, and physiological ageing in comparison with inactive individuals. Methods: This cross-sectional study protocol will examine 112 participants stratified by sex, age (20-35 vs. 65-80 years), and training status (endurance runners vs. inactive controls). Cardiorespiratory fitness (VO2max) is defined as the primary outcome. Secondary outcomes include body composition, musculoskeletal function, biochemical and hormonal markers, and REDs-related screening variables. Assessments will comprise cardiorespiratory testing, DXA-based bone and body composition analysis, isometric knee dynamometry, mobility testing, validated REDs screening tools (LEAF-Q, LEAM-Q, and IOC REDs CAT2), seven-day dietary and training monitoring, venous blood sampling, and skeletal muscle biopsies from the vastus lateralis. Results: This study is designed to generate an integrated overview of physiological, nutritional, metabolic, and muscle-cell characteristics across sex-, age-, and training-specific subgroups. Conclusions: This protocol provides comprehensive insight into how ageing and sex influence endurance physiology and REDs susceptibility and whether long-term endurance training preserves functional capacity across the lifespan. The findings aim to support evidence-based screening, prevention, and targeted interventions for REDs in endurance athletes.